Social Media Influencers, the New Advertising Agency?: Examining the Impact of Social Media Influencer Marketing on the Cosmetics Industry. - Stevenson, Summer; Hack-Polay, Dieu; Tehseen, Shehnaz * (IGI Global, 2022)
This paper examines the impact of social media influencers within the cosmetics industry, with a particular focus on their role as marketing agents. Deutsch and Gerard’s normative social influence theory was used to support the research. This study used a self-completing questionnaire in which respondents were asked to rate their opinions regarding a specific statement on a Likert scale. Qualtrics was used to analyse the data. The results show that influencers can be significant support for business sales. Credibility of influencers was deemed of primary importance to attract customers through social media. However, the authors also found that influencers can damage business reputation, as their brand image—if negative—can contaminate the business brand.